2013
DOI: 10.1016/j.ejca.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy metabolite profiles predict survival in paediatric brain tumours

Abstract: BackgroundBrain tumours cause the highest mortality and morbidity rate of all childhood tumour groups and new methods are required to improve clinical management. 1H magnetic resonance spectroscopy (MRS) allows non-invasive concentration measurements of small molecules present in tumour tissue, providing clinically useful imaging biomarkers. The primary aim of this study was to investigate whether MRS detectable molecules can predict the survival of paediatric brain tumour patients.Patients and methodsShort ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…A tCho/tNAA peak amplitude ratio of at least 2.1 (either at single-voxel spectroscopy with a TE of 144 or 270 msec or at MR spectroscopic imaging with a TE of 280 msec) was found prognostic of unfavorable outcome in pediatric diffuse pontine gliomas (61). Prognostic MR spectroscopy markers are important for treatment stratification and can help identify patients who need more intensive treatment from the outset for some tumor types (47,62,63). These include the detection of 2-hydroxyglutarate in isocitrate dehydrogenase-1 mutated gliomas (47), citrate in proliferating pediatric astrocytomas (62), and highly MR spectroscopy-visible saturated lipids with elevated scylloinositol and low glutamine in high-risk pediatric brain tumors (64).…”
mentioning
confidence: 99%
“…A tCho/tNAA peak amplitude ratio of at least 2.1 (either at single-voxel spectroscopy with a TE of 144 or 270 msec or at MR spectroscopic imaging with a TE of 280 msec) was found prognostic of unfavorable outcome in pediatric diffuse pontine gliomas (61). Prognostic MR spectroscopy markers are important for treatment stratification and can help identify patients who need more intensive treatment from the outset for some tumor types (47,62,63). These include the detection of 2-hydroxyglutarate in isocitrate dehydrogenase-1 mutated gliomas (47), citrate in proliferating pediatric astrocytomas (62), and highly MR spectroscopy-visible saturated lipids with elevated scylloinositol and low glutamine in high-risk pediatric brain tumors (64).…”
mentioning
confidence: 99%
“…As lipids are a marker of poor prognosis in gliomas [10][11][12] the ability to detect them in diagnostic biopsies is likely to be of clinical relevance. Interestingly, there were fewer adipophilin positive tumour cells in all three cases of giant cell glioblastoma when compared to grade four glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid accumulation has been detected in high grade gliomas using ex-vivo nuclear magnetic resonance (NMR) techniques and evidence from electron microscopy and fluorescent labelling with Nile Red has determined that cytoplasmic lipid droplets are the major contributor to this lipid [8,9]. In addition in-vivo magnetic resonance spectroscopy studies of both paediatric and adult brain tumours have reported increased lipids at diagnosis as a marker of poor prognostic outcome [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies are investigating the value of MRS for both diagnostic classification and post-treatment monitoring in brain tumours [4,[13][14][15][16]. However, whilst some studies have correlated clinical information such as tumour grade with MRS features, there are relatively few studies that have directly examined the relationship between in vivo metabolite markers and traditional histopathological measures [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%